Provenance-Based Trust-Aware Requirements Engineering Framework for Self-Adaptive Systems - Lee, Hyo Cheol; Lee, Seok Won (Sensors, 2023)
With the development of artificial intelligence technology, systems that can actively adapt to their surroundings and cooperate with other systems have become increasingly important. One of the most important factors to consider during the process of cooperation among systems is trust. Trust is a social concept that assumes that cooperation with an object will produce positive results in the direction we intend. Our objectives are to propose a method for defining trust during the requirements engineering phase in the process of developing self-adaptive systems and to define the trust evidence models required to evaluate the defined trust at runtime. To achieve this objective, we propose in this study a provenance-based trust-aware requirement engineering framework for self-adaptive systems. The framework helps system engineers derive the user’s requirements as a trust-aware goal model through analysis of the trust concept in the requirements engineering process. We also propose a provenance-based trust evidence model to evaluate trust and provide a method for defining this model for the target domain. Through the proposed framework, a system engineer can treat trust as a factor emerging from the requirements engineering phase for the self-adaptive system and understand the factors affecting trust using the standardized format.
Keywords: Engineering frameworks; Engineering phase; Evidence model; Goal models; Provenance; Requirement engineering; Self-adaptive system; Trust; Trust evidences; Trust-aware; goal modeling; provenance; requirements engineering; self-adaptive system; trust